PERAN DISORGANISASI KELUARGA TERHADAP STRATEGI PEMENUHAN KEBUTUHAN HIDUP ORANG TUA TUNGGAL DI SUMBERSARI, JEMBER - Halimatuz Zahro; Sri Devi Januarifka Fitria; Yuan Amukti Palupi (Cross-border, 2023)
Purpose: This study aims to provide an overview of the role of family disorganization in the strategy of meeting the needs of single parents. Method: This research was conducted using a descriptive descriptive research method. Where the research results are descriptive. Meanwhile, the approach used in this study is a phenomenological approach. Result: Family disorganization is the disintegration of a family that previously played a complete and interconnected role as a unit because each member in it was unable to carry out their obligations and roles in accordance with their social position. This study aims to provide an overview of the role of family disorganization in the strategy of fulfilling the needs of single parents. The conflict process starts from a disorganized family situation. This disorganization is caused by the dysfunction or incompleteness that occurs in a family system. The dysfunctional role of each family member is what causes the family system to be incomplete which then triggers clashes between the two parents. This research implementation uses qualitative research methods. Methods of observation and interviews were used in this study to obtain data regarding the effect of family disorganization on the strategy of fulfilling the needs of single parents, how the impact of division in a family has on the economy of single parents.